Optimisation of the peracetic acid washing disinfection of fresh-cut strawberries based on microbial load reduction and bioactive compounds retention - Van de Velde, Franco (2013)
Total microbial count reduction (TMR), total anthocyanins (TAR), and ascorbic acid retention (AAR) after the operation at different PAA concentrations (0–100 mg L−1), contact times (10–120 s), and temperatures (4–40°C) were used for multiple optimisation using Derringer′s desirability function. Two optimization scenarios (OP 1 and OP 2) were studied. OP 1 was proposed with the goal to maximize TMR with 90% TAR and AAR; and OP 2 maximizing TAR and AAR with TMR of 2 log UFC g−1. The optimized variable levels obtained were the following: 100 mg L−1 PAA, 24 °C and 50 s for OP 1 and 20 mg L−1 PAA, 18 °C and 52 s for OP 2. Additional validation experiments showed agreement between predicted and experimental results. OP 2 conditions are recommended to fresh-cut strawberries washing disinfection because of an acceptable TMR, higher TAR and AAR, better sensory attributes, and the economic convenience of lesser PAA consumption.